ChemInform Abstract: Synthesis, Crystal Structure and Magnetism of Eu3Sc2O5Fe2As2. Issue 48 (December 2015) - Hummel, Franziska; Tegel, Marcus; Gerke, Birgit; Poettgen, Rainer; Johrendt, Dirk
Abstract: The title compound is synthesized from a stoichiometric mixture of Eu, Sc, FeO, and As2 O3 (alumina crucible, 1173 K for 20 h and sintering at 1373 K for 120 h).